Traumatic injuries of the organs of the urinary and male genital system : educational manual - Bachurin, H. V.; Kolomoyets, Y. S.; Бачурін, Георгій Вікторович; Коломоєць, Юлія Сергіївна (Запорізький державний медико-фармацевтичний університет, 2023)
The educational manual for students of IV courses of the II international faculty, majoring in "Medicine", presents theoretical material by topic, practical tasks and test control of knowledge.